Study the Shapes of Nuclei for Heavy Elements with Mass Number Equal to (226â‰¤Aâ‰¤252) through Determination of Deformation Parameters for Two Elements (U&Cf) - Zghaier, Haider A.; Ebrahiem, Sameera A.; Abdul_Jabbar, Hadeel (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2018)
The current paper focuses on the studying the forms of (even-even) nuclei for the heavy elements with mass numbers in the range from (A=226 - 252) for  isotopes. This work will consist of studying deformation parameters  which is deduced from the "Reduced Electric Transition Probability" which is in its turn dependent on the first Excited State . The "Intrinsic Electric Quadrupole Moments" (non-spherical charge distribution)  were also calculated. In addition to that the Roots Mean Square Radii (Isotope Shift) are accounted for in order to compare them with the theoretical results.The difference and variation in shapes of nuclei for the selected isotopes were detected using   3D-plots for them (with symmetric axes); a 2D-plot were also used for each isotope to discriminate between them by the values of semi-major is equal (a) axes and semi minor is equal (b) axes.